2007
DOI: 10.1002/gcc.20505
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of HMGA2 in thyroid carcinomas: A novel molecular marker to distinguish between benign and malignant follicular neoplasias

Abstract: The identification of molecular markers allowing to differentiate between benign and malignant thyroid tumors remains a diagnostic challenge. Herein, we have used the expression of the high mobility group protein gene HMGA2 and its protein, respectively, as a possible marker detecting malignant growth of thyroid tumors. HMGA2 belongs to the high mobility group proteins, i.e. small, highly charged DNA-binding proteins. While HMGA2 is highly expressed in most embryonic tissues, its expression in adult tissues is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
0
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 37 publications
(36 reference statements)
2
73
0
6
Order By: Relevance
“…С одной стороны, выявление белков HMGA2 с помощью иммуногистохимии [25,26] либо экспрессии гена HMGA2 с помощью ОТ-ПЦР [10][11][12]25] в ряде работ позволило достоверно дифференци-ровать злокачественные и доброкачественные опухоли. С другой стороны, есть работы, в которых утвержда-ется, что повышенная экспрессия гена HMGA2 не яв-ляется надежным диагностическим маркером [13,14].…”
Section: экспериментальные статьиunclassified
See 3 more Smart Citations
“…С одной стороны, выявление белков HMGA2 с помощью иммуногистохимии [25,26] либо экспрессии гена HMGA2 с помощью ОТ-ПЦР [10][11][12]25] в ряде работ позволило достоверно дифференци-ровать злокачественные и доброкачественные опухоли. С другой стороны, есть работы, в которых утвержда-ется, что повышенная экспрессия гена HMGA2 не яв-ляется надежным диагностическим маркером [13,14].…”
Section: экспериментальные статьиunclassified
“…Для дан-ной группы образцов уровень экспрессии гена HMGA2 оказался повышен по сравнению с доброкачественны-ми образованиями в среднем в 200 раз, что хорошо согласуется с результатами работы [10]. Повышенная экспрессия HMGA2 выявлена нами в 86 % образцов ПР.…”
Section: экспериментальные статьиunclassified
See 2 more Smart Citations
“…Upregulation or aberrant expression of HMGA2, MET, TPO, TIMP1, DPP4, TFF3, SERPINA1, TIMP1, FN1, TGFA, CRABP1, FCGBP, EPS8 and PROS1 genes have been detected in malignant thyroid tumors [215][216][217][218][219][220]. Diagnostic use of expression levels and profiles of multiple genes have been tested and it is reported that the sensitivity and specificity of these techniques in differential diagnosis of malignant and benign thyroid nodules were 92% and 84%, respectively [221].…”
Section: Molecular Targets In Histopathological Diagnosis and Classifmentioning
confidence: 99%